A Study of the Current Status of Inclusive Education Literacy Development Among College Normal Students Majoring in Early Childhood Education—Taking Province G in China as an Example - Qiuhong Chao (Journal of Advanced Research in Education, 2024)
Inclusive early childhood education is a major trend globally in the pursuit of equitable and high-quality preschool education, and it is an indispensable part of building a high-quality education system in China. Developing an excellent teaching workforce in inclusive early childhood education is key to improving the quality of preschool integration, and pre-service training is particularly crucial. This study focuses on preschool education major students in G Province, China, using a questionnaire survey method to assess the levels of various dimensions of inclusive education literacy among these students, identify existing issues, draw research conclusions, and provide recommendations. The results indicate that students have a high level of understanding of inclusive education concepts, but their knowledge and skills are relatively low. There are significant differences in inclusive education literacy levels among students from different school tiers and grades, with junior college students scoring higher than undergraduate college students. Additionally, there are no significant differences in inclusive education literacy based on gender or whether students have had face-to-face contact with exceptional children. The findings of this study can serve as a valuable resource for the pre-service training of early childhood teachers in inclusive education literacy.